Implementation of the 2013 Curriculum for Science Learning - Rohmatulloh, Ana; Prasetyo, Zuhdan Kun; Pambudi, Haryo Aji (Universitas Pendidikan Indonesia, 2019)
This research aims at describing the 2013 Curriculum implementation for science learning on the planning, classroom implementation, and assessment stages, as well as the obstacles faced by teachers and their efforts to overcome them. This qualitative research was by involving Grade 4 teachers, students, and the principal of a primary school in Yogyakarta as the research subjects. The research object was the activities carried out in the curriculum implementation. The data collection instruments include observation sheets, interview guidelines, questionnaires, and analysis guidelines. The data were analyzed through data reduction, data display, and conclusion. The data validity was tested using triangulation techniques. The research found that the planning stage include studying the syllabus and teacher’s books then outlining the steps of the activities with the scientific approach; the teachers had integrated the science learning with other subjects under a theme; and the scientific approach was employed through observing, questioning, experimenting, associating/reasoning, and communicating. However, the overall implementation of the 2013 Curriculum had not been optimal yet. The teachers had used authentic assessment to assess the students' attitudes, knowledge, and skills, but they rarely used assessment instruments and rubrics. The obstacles faced by teachers were in the planning, classroom implementation, and assessment stages.